Enhancing Chinese EFL Students’ Academic Engagement: The Impact of L2 Enjoyment and Academic Motivation - Wang, Xiaotao (Frontiers in Psychology, 2022)
Students’ personal, emotional, and psychological traits are perceived to be highly influential in their academic engagement; therefore, many investigations have been conducted into the role of students’ characteristics in their level of engagement. Yet, the role of L2 enjoyment and academic motivation as two instances of students’ emotional traits was disregarded. To narrow this gap, this article aimed to assess the effects of these two constructs on Chinese EFL students’ academic engagement. To accomplish this, three pre-designed scales were virtually administered to 490 Chinese students. Using the Spearman Rho test, significant correlations were discovered among the variables. Further, through regression analysis, the predictive power of dependent variables was also assessed. Chinese students’ academic engagement was proved to be favorably predicted by L2 enjoyment and academic motivation. The implications and limitations are finally discussed.